Gender- and Role-Specific Differences in the Perception of the Concept “Impishness” (based on the results of a psycholinguistic experiment) - Iia Gordiienko-Mytrofanova; Iuliia Kobzieva (Психолінгвістика)
The present paper continues a series of articles devoted to ludic competence and the description of its components with the help of psycholinguistic tools and methods. The present article explores another component of ludic competence, i.e. impishness, and the corresponding cultural concept “impishness”.